FRI0662 Assessment of bone density, structure, and cortical interruptions of finger joints in patients with rheumatoid arthritis using high-resolution peripheral quantitative ct. (15th June 2017) - Peters, M; Scharmga, A; Tubergen, A van; Loeffen, D; Weijers, R; Rietbergen, B van; Geusens, P; Bergh, J van den
Abstract : Background: Rheumatoid arthritis (RA) is characterized by peri-articular bone loss. In patients with RA, lower bone density and structural integrity, and an increased number of erosions compared to healthy controls (HCs) has been demonstrated using High-Resolution peripheral Quantitative CT (HR-pQCT) (1, 2). To further characterize RA-related changes, we recently introduced a method for quantifying small cortical interruptions in finger joints (3). Objectives: To investigate the cortical and trabecular bone density, structure, and cortical interruptions in MCP joints in early and late RA patients compared to HCs using HR-pQCT imaging. Methods: The 2nd and 3rd MCP joint of 70 subjects (mean age 53.1 (SD 9.2) years) were evaluated by HR-pQCT (82μm isotropic voxel size): 38 HCs, 10 early RA (diagnosis ≤2 years ago) and 22 late RA (diagnosis ≥10 years ago). Images were analyzed for cortical interruptions, and for cortical and trabecular bone density and structure. Descriptives were analyzed per joint by one-way ANOVA with Bonferroni post-hoc testing or Kruskal-Wallis with Mann-Whitney post-hoc testing, as appropriate. Results: Significant differences with respect to all parameters were found across the groups (Table 1 ). In early and late RA, the percentage of joints with at least 1 interruption was higher, and number of trabeculae, cortical thickness, total density and cortical density were lower than in HC. In addition, in late RA, number of interruptions, interruption volume and trabecular separation were higher, and trabecular density was lower than in HC. Bone loss at the cortical and trabecular bone was primarily observed at the rim of the joint (Figure 1, arrows). Conclusions: Bone density and structural integrity were impaired in early and late RA patients compared to HCs whereas the number of cortical interruptions is increased. The assessment of such parameters using HR-pQCT is, therefore, a promising tool for the follow-up of bone involvement in MCP joints in patients with RA. References: Fouque-Aubert et al., ARD 2010. Stach et al., A&R 2010. Peters et al., ACR2016 (abstract). Disclosure of Interest: M. Peters: None declared, A. Scharmga: None declared, A. van Tubergen: None declared, D. Loeffen: None declared, R. Weijers: None declared, B. van Rietbergen Consultant for: Scanco Medical AG, P. Geusens: None declared, J. van den Bergh: None declared